The Java Workshop: A New, Interactive Approach to Learning Java - David Cuartielles, Cuartielles; Andreas Goransson, Goransson; Eric Foster-Johnson, Foster-Johnson (Packt Publishing, 2019)
Cut through the noise and get real results with a step-by-step approach to learning Java programmingKey FeaturesIdeal for the Java beginner who is getting started for the first timeA step-by-step Java tutorial with exercises and activities that help build key skillsStructured to let you progress at your own pace, on your own termsUse your physical copy to redeem free access to the online interactive editionBook DescriptionYou already know you want to learn Java, and a smarter way to learn Java 12 is to learn by doing. The Java Workshop focuses on building up your practical skills so that you can develop high-performance Java applications that work flawlessly within the JVM across web, mobile and desktop. You'll learn from real examples that lead to real results.Throughout The Java Workshop, you'll take an engaging step-by-step approach to understanding Java. You won't have to sit through any unnecessary theory. If you're short on time you can jump into a single exercise each day or spend an entire weekend learning about Reactive programming and Unit testing. It's your choice. Learning on your terms, you'll build up and reinforce key skills in a way that feels rewarding.Every physical copy of The Java Workshop unlocks access to the interactive edition. With videos detailing all exercises and activities, you'll always have a guided solution. You can also benchmark yourself against assessments, track progress, and receive free content updates. You'll even earn a secure credential that you can share and verify online upon completion. It's a premium learning experience that's included with your printed copy. To redeem, follow the instructions located at the start of your Java book.Fast-paced and direct, The Java Workshop is the ideal companion for Java beginners. You'll build and iterate on your code like a software developer, learning along the way. This process means that you'll find that your new skills stick, embedded as best practice. A solid foundation for the years ahead.What you will learnGet to grips with fundamental concepts and conventions of Java 12Write clean and well-commented code that's easy to maintainDebug and compile logical errors and handle exceptions in your programsUnderstand how to work with Java APIs and Java streamsLearn how to use third-party libraries and software development kits (SDKs)Discover how you can work with information stored in databasesUnderstand how you can keep data secure with cryptography and encryptionLearn how to keep your development process bug-free with unit testing in JavaWho this book is forOur goal at Packt is to help you be successful, in whatever it is you choose to do. The Java Workshop is an ideal Java tutorial for the Java beginner who is just getting started. Pick up a Workshop today, and let Packt help you develop skills that stick with you for life.